Perfil nutricional de pacientes em pré-operatório eletivo para câncer colorretal - Luiza Regina Lima Soares Barbosa (2011)
Cancer is one of the most lethal diseases in the world, being the second leading cause of death, including Brazil. Among cancers, colorectal carcinoma (CRC) is one of the most prevalent and often subject to surgical cure. Weight loss and malnutrition are nutritional disturbances frequently observed in cancer patients and are associated with higher postoperative morbidity and mortality. Early diagnosis of malnutrition has been gaining increasing importance in the surgical clinic, as many nutritional deficiencies can be corrected preoperatively. Few data are available on the preoperative nutritional status on an outpatient basis of patients with CRC. This investigation was designed to identify the preoperative nutritional status of patients with CRC, through direct and indirect methods of nutritional assessment. We evaluated 66 consecutive patients with CRC candidates for elective surgical treatment in relation to clinical history, socio-demographic data, eating habits and nutritional status, which was assessed by direct methods (anthropometry) and indirect (subjective global assessment - SGA). The study sample was mostly older, female, married, with education up to primary education and monthly income of up to five minimum wages. Most of patients had colon tumors and disease stage II. Food intake is decreased in relation to recommended and showed statistical difference in malnourished patients. Malnutrition ranged from 7.6 to 53 per cent and, according to the SGA, 36.4 per cent of this population showed malnutrition. The prevalence of malnutrition was greater in females, in those patients with abnormal appetite and who have had weight loss. SGA showed poor correlation with the other methods evaluated in this study. The prevalence of malnutrition in patients with CRC was approximately one third of the population examined, but no single method could be considered with good accuracy in identifying malnutrition. Despite this limitation, the early and full nutritional assessment is needed to identify malnutrition in preoperative patients with CRC, so that appropriate measures could be taken to minimize the occurrence of postoperative complications.